Generation of an inverting herpes simplex virus 1 mutant lacking the L-S junction a sequences, an origin of DNA synthesis, and several genes including those specifying glycoprotein E and the alpha 47 gene. - Longnecker, R (1986)
The herpes simplex virus genome consists of two components, L and S, that invert relative to each other to yield four isomeric arrangements, prototype (P), inversion of the S component (Is), inversion of the L component (Il), and inversion of both components (Isl). Previous studies have shown that the 500-base-pair a sequences flanking the two components contain a cis-acting site for inversion. In an attempt to insert a third copy of the alpha 4 gene, the major regulatory gene mapping in the repeats flanking the S component, a fragment containing the alpha 4 gene and an origin of DNA synthesis, was recombined into the thymidine kinase gene mapping in the unique sequences of the L component. The resulting recombinants showed massive rearrangements and deletions mapping in the S component and in the junction between the L and S components. One recombinant (R7023) yielded two isomeric DNA arrangements, a major component consisting of Is and a minor component consisting of Isl. In these arrangements, the genome lacked the gene specifying glycoprotein E and all contiguous genes located between it and the alpha 0 gene in the inverted repeats of the L component. Among the deleted sequences were those encoding an origin of viral DNA synthesis, the alpha 47 gene, and the a sequences located at the junction between the L and S-components. The recombinant grew well in rabbit skin, 143TK-, and Vero cell lines. We conclude that the four unique genes deleted in R7023 are not essential for the growth of herpes simplex virus, at least in the cell lines tested, and that the b sequence of the inverted repeats of the L component also contains cis-acting sites for the inversion of herpes simplex virus DNA sequences.